Polyoxazolidone derivatives and their use in medical devices

JP2026536522APending Publication Date: 2026-10-30ユニヴェルシテドリエージュ
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026522531
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-10-04
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

【0012】 医療用途、特に血液接触デバイスに対するPHOxの他の利点は、良好な生体適合性及び血液適合性である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026536522000001_ABST
    Figure 2026536522000001_ABST
Patent Text Reader

Abstract

The present invention relates to a poly(hydroxyoxazolidone) compound (PHOx) corresponding to the following formula (I) or formula (II): where R1 and R2 are each independently of each other a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, -R3 and R4 are each independently of each other a hydrogen or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, -R5, R 5’ , R6, R 6’ Each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group, and -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, preferably having 1-20, more preferably 1-12, most preferably 1-8 carbon atoms, and optionally further containing one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes, and -Optionally, A, R3, and R4 in formula (I) are linked to each other to form a cyclic structure, and -Optionally, R5 and R in formula (II) 5’ , and / or R6 and R 6’ The present invention provides a poly(hydroxyoxazolidone) compound (PHOx) in which each of the elements is linked to form a cyclic structure, -R7 is a polymer chain selected from polysiloxane or polyether, and -n is an integer from 2 to 100, preferably 2 to 50, more preferably 2 to 25, and most preferably 2 to 15. The present invention further provides a process for forming the PHOx compound of the present invention, and a poly(alkylideneoxazolidone) compound (POx) obtained by dehydrating the PHOx compound of the present invention. [Formula 1] JPEG2026536522000051.jpg140170
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to formulations for poly(oxazolidone) derivatives, processes for obtaining said poly(oxazolidone) derivatives, and the use of said poly(oxazolidone) derivatives in medical devices. [Background technology]

[0002] Medical devices (MDs) are used clinically in a variety of applications, and their performance is crucial to the overall health and quality of life of patients. However, implantable blood-contact MDs are susceptible to thrombosis and / or infection. Foreign objects in contact with blood can trigger the host's inflammatory response, adhesion of plasma proteins and platelets, and activation of contact pathways in the coagulation cascade. In addition, the surface of the MD can become colonized by bacteria or fungi, ultimately leading to local or systemic infection. Such colonization can occur at the moment of implantation or much later (hematogenous infection). Eliminating the infection is extremely difficult because a bacterial biofilm forms on the surface of the device. Prompt treatment of the patient with antithrombotic agents or antibiotics is rarely effective, and removal of the MD is often the only solution.

[0003] Furthermore, complications such as bleeding (associated with antithrombotic therapy) and antibiotic resistance (associated with antibiotic therapy) may occur. Therefore, when considering MD implantation, the best management approach is prevention.

[0004] Biocompatibility refers to whether, if present, the implant material or its degradation products initiate a harmful tissue response in the host, or conversely, whether harmful changes in the chemical, physical, or mechanical properties of the implant material are caused by the host environment. The term "blood compatibility" refers to biocompatibility issues related to implantation in the cardiovascular system, such as any toxicity of the implant material to red blood cells or tissues in contact with the material.

[0005] Catheters are one of the most frequently implanted blood-contacting medical devices that are in need of such improvements. In fact, thrombotic and infectious complications associated with catheter use occur frequently (with thrombosis in up to 66% of catheter implantations, and infection in up to 8%), which leads to longer hospital stays, higher medical costs, or even death. A catheter is a thin tube made primarily of polyurethane (PU), but also of other medical-grade plastics such as silicone rubber, polyvinyl chloride, or nylon, which is inserted into a patient's body cavity, duct, or blood vessel to deliver drugs or drain bodily fluids for therapeutic, diagnostic, and / or monitoring purposes. Catheters have a wide range of clinical applications, including cardiovascular, urological, gastrointestinal, neurovascular, and ophthalmic uses. There is high demand for peripheral intravenous and central venous catheters, which are intravascular catheters intended to ensure the safe infusion of fluids or drugs for short-term or long-term use (several months to several years).

[0006] Other blood-contacting medical devices are artificial heart valves. As the prevalence of heart valve disease is steadily increasing, it is estimated that more than 1 million patients will require heart valve replacement by 2050. There are two main types of artificial heart valves: mechanical valves and bioprosthetic valves. Mechanical prostheses are made primarily of pyrolytic carbon combined with metallic and polymeric components. However, mechanical artificial heart valves are associated with the challenge of thrombus formation. The incidence of prosthetic valve thrombosis is reported to average 0.2% per patient-year after aortic valve replacement and 1.8% per patient-year after mitral valve replacement, with a wide reported range from less than 0.1% to over 6% per patient-year. The risk of prosthetic valve thrombosis appears to be about twice as high in mitral valve replacement as in aortic valve replacement, and more than three times higher for tricuspid valve prostheses.

[0007] Bioprostheses made of porcine valves or bovine pericardium are less thrombotic, but they are prone to degradation. Accordingly, the available artificial valve options that exist today have several limitations. In addition, the costs and materials required to source and process biological tissues limit the widespread use of bioprosthetic valves in low-resource settings.

[0008] Early attempts to develop polymer heart valves were largely unsuccessful due to the limited ability to modify polymeric compounds to meet the needs of an ideal heart valve replacement. Various materials have been investigated as candidates for polymer heart valves, including poly(tetrafluoroethylene), polysiloxanes, poly(styrene-b-isobutylene-b-styrene), and polyurethanes. However, these polymers have limited blood compatibility, or undergo calcification and / or degradation and / or weakening over time.

[0009] Accordingly, there exists a need to develop biocompatible materials that are suitable for use in medical devices and that solve one or more of the problems outlined above. SUMMARY OF THE INVENTION

[0010] According to a first aspect, the present invention relates to a poly(hydroxyoxazolidone) compound (PHOx) corresponding to the following formula (I) or formula (II): Chemical Formula which is wherein -R 1’ , R 2’ each independently represent a C1 to C20 alkyl group, preferably a C1 to C10 alkyl group, more preferably a C1 to C3 alkyl group, most preferably a methyl group, -R3 and R4 each independently represent hydrogen, or a C1 to C20 alkyl group, preferably a C1 to C10 alkyl group, more preferably a C1 to C3 alkyl group, most preferably a methyl group, -R5, R 5’ , R6, R 6’ each independently represent hydrogen, or a C1 to C20 alkyl group, preferably a C1 to C10 alkyl group, more preferably a C1 to C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group, -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, which preferably have 1 to 20 carbon atoms, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further contain one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. -Optionally, A, R3, and R4 in equation (I) are connected to each other to form a ring structure. -Optionally, R5 and R in equation (II) 5’ , and / or R6 and R 6’ However, they are each connected to each other to form a ring structure, -R7 is a polymer chain selected from polysiloxane or polyether. The present invention provides a poly(hydroxyoxazolidone) compound (PHOx) in which -n is an integer between 2 and 100, preferably between 2 and 50, more preferably between 2 and 25, and most preferably between 2 and 15.

[0011] Advantageously, the monomer unit of PHOx according to the present invention consists of a relatively short and rigid cyclic group on one side and a relatively long and flexible segment on the other side, the latter derived from a polymer chain. This provides PHOx with unique properties such as easy (re)processing, high thermal stability, low water absorption, and stability over time.

[0012] Other advantages of PHOx for medical applications, particularly blood contact devices, include good biocompatibility and hemocompatibility.

[0013] The present invention further provides a formulation for forming poly(hydroxyoxazolidone) (PHOx), the formulation comprising: at least one polyfunctional cyclic carbonate (compound A) having at least two terminal α-alkylidene cyclic carbonate groups; and at least one polyfunctional primary amine (compound B), wherein the polyfunctional amine is composed of a polymer chain, the polymer chain having at least two primary amine groups at its terminals, and the polymer chain is selected from polysiloxane or polyether.

[0014] The present invention further relates to a process for forming the poly(hydroxyoxazolidone).

[0015] According to a second aspect, the present invention relates to a poly(alkylidene oxazolidone) compound (POx), wherein the poly(alkylidene oxazolidone) compound (POx) is preferably obtained by dehydrating a poly(hydroxyoxazolidone) compound (PHOx) according to a first aspect of the present invention. The poly(alkylidene oxazolidone) compound (POx) has the following formula: (V) or (VI): [ka] In response to, During the ceremony, -R1, R2, R8, and R9 each independently represent hydrogen or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably hydrogen. -R3 and R4 each independently represent hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R5, R 5’ , R6, R 6’each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group, -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or araliphatic hydrocarbon groups, having preferably 1 to 20, more preferably 1 to 12, most preferably 1 to 8 carbon atoms, and optionally further containing one or more functional groups selected from ether, ester, amide, amine, carboxyl, sulfur, halogen, and / or urethane, -optionally, A, R3, and R4 in formula (V) are linked to each other to form a cyclic structure, -optionally, R5 and R in formula (VI) 5’ and / or R6 and R 6’ are each linked to each other to form a cyclic structure, -R7 is a polymer chain selected from polysiloxane or polyether, -n is an integer of 2 to 100, preferably 2 to 50, more preferably 2 to 25, most preferably 2 to 15.

[0016] According to a third aspect, the present invention provides formulations and methods for crosslinking the poly(alkylidene oxazolidone) compound according to the second aspect of the present invention to form a biocompatible poly(oxazolidone) network. The crosslinking method is preferably selected from thiol-ene reactions, and the poly(alkylidene oxazolidone) compound reacts with a polythiol, and optionally a suitable radical and / or cationic polymerization initiator, more preferably a radical and / or cationic polymerization (photo)initiator, to form a crosslinked poly(oxazolidone), which surprisingly exhibits very good biocompatibility and very good mechanical resistance (especially when compared, for example, with existing PU compounds). They also exhibit hemocompatibility characteristics similar to medical-grade PUs used in medical devices that come into contact with blood.

[0017] These and further aspects of the present invention, as well as preferred embodiments, are described in the following sections and in the appended claims. The subject matter of the appended claims is hereby specifically incorporated herein.

[0018] Description of the Embodiment For clarity and concise explanation, features are described herein as part of the same or distinct embodiments, but it should be understood that the scope of the invention may include embodiments having all or some combinations of the described features.

[0019] The technical terms used to describe specific embodiments are not intended to limit the invention. Where used herein, the singular forms “a,” “an,” and “the” are also intended to include plural forms unless the context clearly indicates otherwise. The term “and / or” includes any and all combinations of one or more of the associated enumerated items. The terms “comprises” and / or “comprising” specify the presence of the described features but should not be understood as excluding the presence or addition of one or more other features. Furthermore, unless otherwise specified, where it is mentioned that a particular step of a method follows another step, it should be understood that it may proceed directly to that other step or one or more intermediate steps may be performed before the particular step is performed.

[0020] As used herein, the term “polymer chain” refers to a molecular chain consisting of at least three repeating units.

[0021] As used herein, the term "polyether" refers to a polymer chain in which at least three repeating units contain ether bonds.

[0022] As used herein, the term “medical device” (also referred to herein as “MD”) means all implantable foreign bodies for clinical use in a host mammal, including artificial joints, pacemakers, pacemaker leads, implantable defibrillators, vascular catheters, intravascular catheters or urethral catheters, stents including coronary stents, components of extracorporeal membrane oxygenation systems or other medical tubing, blood bags and wound healing products, cardiac devices, artificial heart valves, left ventricular assist device chambers, artificial hearts, intraocular lenses, dental implants, breast implants, endotracheal tubes, and gastrostomy tubes. Medical devices according to the present invention also mean non-implantable devices such as blood bags, wound healing products, and components of extracorporeal membrane oxygenation systems. Medical devices also include patches for managing infarcted cardiac tissue.

[0023] As used herein, the term “host mammal” refers to humans, but may also refer to animals.

[0024] As used herein, the term “thiol-ene” reaction refers to the addition of a thiol radical and / or cationic catalyst to a vinyl functional group, thereby producing a crosslinked poly(oxazolidone) network, a crosslinked poly(oxazolidone) compound, or a crosslinked oxazolidone polymer network, also referred herein as a crosslinked poly(oxazolidone). The “thiol-ene” reaction may be enhanced by the presence of a photoinitiator or a radical and / or cationic polymerization initiator, such as a conventional radical and / or cationic initiator.

[0025] As used herein, the terms "weight %", "weight percentage", or "percentage by weight" refer to the mass fraction of a compound in a mixture, expressed as a percentage between 0 and 100, divided by the total mass of the mixture.

[0026] According to a first aspect of the present invention, a poly(hydroxyoxazolidone) compound (PHOx) is provided, wherein the compound is of formula (I) or (II): [ka] In response to, During the ceremony, -R 1’ , R 2’ However, each independently represents a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R3 and R4 each independently represent hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R5, R 5’ , R6, R 6’ However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group. -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, preferably having 1 to 20 carbon atoms, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further containing one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. -Optionally, A, R3, and R4 in equation (I) are connected to each other to form a ring structure. -Optionally, R5 and R in equation (II) 5’ , and / or R6 and R 6’ However, they are each connected to each other to form a ring structure, -R7 is a polymer chain selected from polysiloxane or polyether. -n is an integer between 2 and 100, preferably between 2 and 50, more preferably between 2 and 25, and most preferably between 2 and 15.

[0027] According to a preferred embodiment, the poly(hydroxyoxazolidone) compound (PHOx) is the following compound: [ka] Corresponding to the formula, -R 1’ , R 2’ However, each independently represents a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R7 is a polymer chain selected from polysiloxane or polyether. -n is an integer between 2 and 100, preferably between 2 and 50, more preferably between 2 and 25, and most preferably between 2 and 15.

[0028] According to the embodiment, the polymer chain is selected from polysiloxane, preferably polydimethylsiloxane (PDMS). The polysiloxane may have a molecular weight in the range of 250 to 50,000 g / mol, preferably 900 to 30,000 g / mol, preferably 1,000 to 20,000 g / mol, more preferably 1,500 to 10,000 g / mol, more preferably 2,000 to 5,000 g / mol, and most preferably 2,000 to 3,000 g / mol.

[0029] According to the embodiment, the polymer chain is selected from polyalkylene glycol, preferably polytetrahydrofuran (poly(tetramethylene ether) glycol), polypropylene glycol (PPG), or polyethylene glycol (PEG) polyether. The polyether may have a molecular weight in the range of 230 to 50,000 g / mol, preferably 230 to 10,000 g / mol, more preferably 230 to 5,000 g / mol, more preferably 300 to 4,000 g / mol, and most preferably 350 to 3,000 g / mol.

[0030] The present invention further relates to a formulation for preparing a poly(hydroxyoxazolidone), such as a poly(hydroxyoxazolidone) according to formula (I) or (II), wherein the formulation is -Formula (III) or (IV): [ka] A polyfunctional cyclic carbonate (compound A) having at least two terminal α-alkylidene cyclic carbonate groups, During the ceremony, -R1, R2, R8, and R9 each independently represent hydrogen or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably hydrogen. -R3 and R4 each independently represent hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R5, R 5’ , R6, R 6’ However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group. -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, preferably having 1 to 20 carbon atoms, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further containing one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. -Optionally, A, R3, and R4 in equation (III) are connected to each other to form a ring structure. -Optionally, R5 and R in equation (IV) 5’ , and / or R6 and R 6’ However, each is linked to the others to form a cyclic structure, and there is at least one polyfunctional cyclic carbonate (compound A), The present invention provides a formulation comprising at least one polyfunctional amine (compound B), wherein the polyfunctional amine is composed of a polymer chain, the polymer chain having at least two primary amine groups at its termini, and the polymer chain being selected from polysiloxane or polyether.

[0031] In alternative embodiments, a polyfunctional cyclic carbonate compound may be prepared first using formulations of compounds A and B listed above, comprising a polymer chain bonded to at least two terminal α-alkylidene cyclic carbonate groups via oxazolidone bonds. Thus, the polymer chain of the polyfunctional amine is inserted into the polyfunctional cyclic carbonate. Such polymer compound A can then be polymerized in a second step with a second polyfunctional amine (compound C) to form an alternative PHOx in which the organic linking group A comprises a polymer chain selected from polysiloxane or polyether, and R7 is a C1-C20 alkyl or aryl group.

[0032] Advantageously, formulations of compounds A and B listed above further include compound C. Compound C may be selected from relatively short and / or rigid polyfunctional amines, in contrast to the polymeric polyfunctional amine of compound B. Compound C is, for example, one of the following: [ka]

[0033] The present invention further provides a process for forming poly(hydroxyoxazolidone) compounds, such as poly(hydroxyoxazolidone) compounds according to formula (I) or (II), the process comprising at least a polyaddition step between a polyfunctional cyclic carbonate (compound A) and a polyfunctional amine (compound B).

[0034] Polyfunctional cyclic carbonate (Compound A) The polyfunctional cyclic carbonate according to the present invention, used to form the poly(hydroxyoxazolidone) of the present invention, has at least two terminal α-alkylidene cyclic carbonate groups and is also referred to herein as α-alkylidenebis (cyclic carbonate).

[0035] The polyfunctional cyclic carbonate according to the present invention is of formula (III) or (IV): [ka] In response to, In the formula, R1, R2, R3, R 4、 R5, R 5’ , R6, R 6’、 R8, R9, and A are as described above.

[0036] According to a preferred embodiment, R1 and R2 can be independently selected from preferably C1-C10 alkyl groups, C1-C6 alkyl groups, C1-C3 alkyl groups, methyl groups, or particularly preferably hydrogen.

[0037] According to a preferred embodiment, the polyfunctional cyclic carbonate is the following compound: [ka] Corresponding to the formula, R1, R2, R8, and R9 each independently represent hydrogen or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, and most preferably hydrogen.

[0038] According to a preferred embodiment, the polyfunctional cyclic carbonate according to the present invention is of formula (III): [ka] In response to, In the formula, R1, R2, R8, and R9 are independently selected from preferably C1-C10 alkyl groups, C1-C6 alkyl groups, C1-C3 alkyl groups, methyl groups, or particularly preferably hydrogen, and R3 and R4 can be independently selected from preferably C1-C10 alkyl groups, C1-C6 alkyl groups, C1-C3 alkyl groups, or particularly preferably hydrogen.

[0039] According to a preferred embodiment, the polyfunctional cyclic carbonate according to the present invention is of formula (IV): [ka] In response to, In the formula, R5', R5, R6', and R6 are independently selected from preferably C1-C10 alkyl groups, C1-C6 alkyl groups, C1-C3 alkyl groups, methyl groups, or particularly preferably methyl groups.

[0040] In a preferred embodiment, R3 and R4 preferably represent a C1-10 alkyl group, a C1-C6 alkyl group, a C1-C3 alkyl group, or hydrogen, particularly preferably a methyl group. R1, R2, R8, and R9 particularly preferably represent hydrogen, or R1, R2, R8, and R9 represent hydrogen and R3 represents a methyl group.

[0041] According to a preferred embodiment, R 5、 R6, R 5’ , and R 6’ These terms preferably have the same meaning.

[0042] In a preferred embodiment, R1 preferably has the same meaning as R2, R8 preferably has the same meaning as R9, and R4 preferably has the same meaning as R3.

[0043] According to a preferred embodiment, A is preferably an organic linking group selected from alkylene groups having 1 to 6 carbon atoms, such as butylene, propylene, ethylene, or particularly preferably methylene, and may further comprise one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes.

[0044] Preferred examples of α-alkylidenebis (cyclic carbonates) correspond to formula III and the following compounds (also referred to herein as BisαCC1 (left) and BisαCC2 (right)). [ka]

[0045] Further preferred examples of α-alkylidenebis (cyclic carbonate) corresponding to formula III are the following compounds. [ka]

[0046] A suitable example of α-alkylidenebis (cyclic carbonate) corresponds to formula IV and corresponds to the following compounds. [ka]

[0047] Polyfunctional polymer amine (compound B) The polyfunctional polymer amine according to the present invention, used to form the poly(hydroxyoxazolidone) of the present invention, is preferably selected from polymer diamines, wherein the diamine contains a polymer chain, and the polymer chain has at least two primary amine groups at its terminals.

[0048] Preferably, such polymer diamines correspond to the formula NH2-R7-NH2, where R7 is composed of a polymer chain selected from polysiloxane or polyether.

[0049] Preferred polyfunctional polymer amines are selected from polymer diamines comprising polymer chains selected from polydimethylsiloxane (PDMS), polypropylene glycol (PPG), polytetrahydrofuran (PTHF), or polyethylene glycol (PEG), and having at least two primary amine groups at the ends of the polymer chains.

[0050] According to a preferred embodiment, the polymer chain is selected from polysiloxane, preferably PDMS. The polysiloxane has a molecular weight preferably in the range of 250 to 50,000 g / mol, preferably 900 to 30,000 g / mol, preferably 1,000 to 20,000 g / mol, preferably 1,500 to 10,000 g / mol, more preferably in the range of 2,000 to 5,000 g / mol, and most preferably in the range of 2,000 to 3,000 g / mol.

[0051] In alternative embodiments, the polyfunctional amine is composed of a polymer chain selected from a polyether, preferably a polyalkylene glycol. The polyalkylene glycol is preferably selected from polytetrahydrofuran, or (poly(tetramethylene ether) glycol) (PTHF), polypropylene glycol (PPG), or polyethylene glycol (PEG). The polyether has a molecular weight preferably in the range of 230 to 50,000 g / mol, preferably 230 to 10,000 g / mol, preferably 230 to 5,000 g / mol, more preferably 300 to 4,000 g / mol, and most preferably 350 to 3,000 g / mol.

[0052] Examples of suitable polymer diamines containing polymer chains, wherein the polymer chain contains at least two primary amines at its terminals, include the commercially available Jeffamine® ED series, Jeffamine® D series, and Jeffamine® M series from Huntsman.

[0053] The use of polymer diamines, in which the polymer chain is selected from polysiloxanes such as PDMS, results in poly(hydroxyoxazolidone) with elastomeric properties.

[0054] The use of polymer diamines, in which the polymer chain is selected from polyethers such as PPG, PTHF, or PEG, results in a poly(hydroxyoxazolidone) that is more hydrophilic compared to poly(hydroxyoxazolidone) prepared using polysiloxanes such as PDMS. The use of PDMS in formulations for producing poly(hydroxyoxazolidone) results in a poly(hydroxyoxazolidone) that is more hydrophilic. Therefore, hydrophilic-hydrophobic properties can be advantageously adapted.

[0055] Preferred examples of PPG and PEG-based polymer diamines according to the present invention (also referred to herein as PPG-NH2 and PEG-NH2) are: [ka] In the formula, m is an integer in the range of 3 to 1000, preferably 3 to 300, and more preferably 3 to 112.

[0056] A preferred example of a PDMS-based polymer diamine (also referred to herein as PDMS-NH2) according to the present invention is: [ka] In the formula, m is an integer in the range of 3 to 1000, preferably 6 to 500, and more preferably 8 to 362.

[0057] Specific examples of suitable diamines are as follows: [ka]

[0058] Polyaddition step (between compound A and compound B) Examples of polyaddition reactions according to the present invention are as follows: [ka]

[0059] Some possible examples of polyhydroxyoxazolidone according to the present invention are as follows: [ka] In the formula, m is between 3 and 112, and n is between 8 and 362.

[0060] According to a preferred embodiment, the polyaddition step is carried out by reacting a polyfunctional cyclic carbonate (compound A) and a polyfunctional amine (compound B) by mixing them, optionally in the presence of an organic solvent, preferably under a nitrogen atmosphere, at a temperature in the range of 25 to 100°C, preferably 60 to 90°C. If a solvent is used, the solvent may be selected from organic solvents such as chloroform or dichloromethane.

[0061] According to a second aspect of the present invention, a poly(alkylidene oxazolidone) compound is provided, the compound having formula (V) or (VI): [ka] In response to, During the ceremony, -R1, R2, R8, and R9 each independently represent hydrogen or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably hydrogen. -R3 and R4 each independently represent hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R5, R 5’ , R6, R 6’However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group. -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, which preferably have 1 to 20 carbon atoms, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further contain one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. -Optionally, A, R3, and R4 in equation (V) are connected to each other to form a ring structure. -Optionally, R5 and R in equation (VI) 5’ , and / or R6 and R 6’ However, they are each connected to each other to form a ring structure, -R7 is a polymer chain selected from polysiloxane or polyether. -n is an integer between 2 and 100, preferably between 2 and 50, more preferably between 2 and 25, and most preferably between 2 and 15.

[0062] According to a preferred embodiment, the poly(alkylidene oxazolidone) compound according to the present invention is of formula (V): [ka] In response to, In the formula, R1, R2, R3, R4, R7, R8, and R9, A, and n are as defined above, and particularly preferably R1, R2, R8, and R9 represent hydrogen, and R3 and R4 represent methyl groups.

[0063] According to a preferred embodiment, the poly(alkylidene oxazolidone) compound according to the present invention is of formula (VI): [ka] In response to, In the formula, R 5、R6, R 5’ , and R 6’、 R7, A, and n are as defined above.

[0064] The present invention further provides a process for forming a poly(alkylideneoxazolidone) compound corresponding to formula (V) or (VI), the process comprising at least a step of dehydrating a poly(hydroxyoxazolidone) compound, such as a poly(hydroxyoxazolidone) compound according to a first aspect of the present invention.

[0065] Dehydration step The dehydration step may optionally be carried out in an oven under vacuum conditions at a temperature in the range of 100°C to 200°C, preferably 100°C to 160°C, for example, 130°C, for at least 1 hour, most preferably 2 hours, preferably under conditions free of solvent and catalyst.

[0066] An example of the dehydration reaction according to the present invention is as follows: [ka]

[0067] Alternatively, dehydration may be carried out by reflux, in which the polymer is dispersed in glacial acetic acid for 2 hours, and then the acetic acid is removed from the polymer. After the polymer has been solubilized in an organic solvent (DMF, DMSO, etc.), an alternative acid such as methanesulfonic acid and / or sulfuric acid may be used to dehydrate the polymer.

[0068] According to a third aspect, the present invention provides formulations and methods for crosslinking poly(alkylidene oxazolidone) compounds according to a second aspect of the present invention to form a biocompatible poly(oxazolidone) network. The crosslinking method is selected from thiol-ene reactions, in which the poly(alkylidene oxazolidone) compound reacts with a polythiol and, optionally, a suitable radical / cationic polymerization initiator, preferably a radical / cationic polymerization photoinitiator or a radical / cationic polymerization thermal initiator, to form crosslinked poly(oxazolidone), which surprisingly exhibited biocompatibility and very good mechanical resistance. They also surprisingly showed high hemocompatibility, making them particularly suitable candidates for use in any medical device that comes into contact with blood.

[0069] According to the embodiment, the crosslinkable formulation for forming a network of poly(oxazolidone) compounds is -At least one poly(alkylideneoxazolidone) compound according to a second aspect of the present invention, -Formula R 10 -SH x At least one polythiol corresponding to, where R 10 However, it is an organic group selected from C4-C20 alkyl groups, and optionally further contains one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes, and at least one polythiol in which x is an integer from 2 to 8, preferably from 2 to 6. -A radical polymerization initiator, optionally selected from radical photopolymerization initiators and / or radical thermal polymerization initiators and / or redox radical initiators, -Optionally selected, preferably from cationic photopolymerization initiators and / or thermal cationic polymerization initiators, -Optionally includes a combination of radical and cationic initiators.

[0070] The present invention provides a crosslinking reaction for a crosslinkable formulation for forming a network of poly(oxazolidone) compounds, wherein the crosslinking step is preferably selected from radical and / or cationic polymerization, more specifically from a thiol-ene reaction, in which the poly(alkylidene oxazolidone) compound reacts with a polythiol and, optionally, a suitable radical and / or cationic polymerization initiator.

[0071] The crosslinked poly(oxazolidone) compounds according to the present invention, which are crosslinked by cationic polymerization using a cationic polymerization initiator, tend to be more flexible and more suitable for use in medical applications requiring flexibility, such as heart valves.

[0072] The crosslinked poly(oxazolidone) compound according to the present invention, which is crosslinked by cationic polymerization using a cationic polymerization initiator, is reusable due to the presence of dynamic bonds.

[0073] The present invention also provides recyclable crosslinked poly(oxazolidone) obtained by the process described above, preferably in the presence of a cationic polymerization initiator selected from acids such as methanesulfonic acid, sulfuric acid, p-toluenesulfonic acid, and combinations thereof.

[0074] The present invention further provides a process for recycling the above-mentioned cross-linked poly(oxazolidone) by injection molding, extrusion molding, and additive manufacturing of extrusion-based materials, or by chemical recycling.

[0075] Preferably, the thiol-ene reaction is carried out at room temperature by irradiation with light (UV, red, and / or visible light range), and the initiator is selected from photopolymerization initiators.

[0076] The crosslinking described herein may also be referred to as curing or networking. Crosslinking formulations also mean curing formulations.

[0077] Cross-linked poly(oxazolidone) compounds are ideally suited for use in medical devices where biocompatibility is required.

[0078] Polythiol Suitable polythiols for use in crosslinking formulations for creating crosslinked poly(oxazolidone) networks refer to compounds containing two or more thiol functional groups (-SH).

[0079] The polythiol used in this invention is of formula R 10 -SH x The formula includes the materials, in which R 10 R is the organic part, and x is at least 2, typically an integer between 2 and 6. Such polythiols may include, for example, reaction products of thiol-functional organic acids and polyols. Thus, the organic part R 10 It may contain an ester group and / or be derived from a polyol.

[0080] Therefore, suitable examples of polythiols that can be used in the crosslinkable composition according to the present invention include, for example, esters of thiol-containing acids.

[0081] Suitable examples of polythiols: [ka]

[0082] Initiators for crosslinking The crosslinkable formulation of the present invention, used to form the crosslinked (biocompatible) poly(alkylidene oxazolidone) of the present invention, may contain a radical or cationic polymerization initiator in the thiol-ene reaction.

[0083] According to the embodiment, a radical polymerization initiator refers to one that generates radicals through heat, (UV) light, oxidation-reduction reactions, etc. Therefore, the reaction initiator can be selected from photopolymerization initiators and / or thermal polymerization initiators.

[0084] Suitable radical thermal polymerization initiators include organic peroxides, azo compounds, and redox initiators.

[0085] Examples of organic peroxides include benzoyl peroxide, cumene hydroperoxide, di-tert-butyl peroxide, tert-butyl hydroperoxide, and dicumyl peroxide.

[0086] Specific examples of azo compounds include 2,2'-azobispropane, 2,2'-dichloro-2,2'-azobispropane, 1,1'-azo(methylethyl)diacetate, 2,2'-azobisisobutane, 2,2'-azobisisobutylamide, 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylpropionate methyl, 2,2'-dichloro-2,2'-azobisbutane, 2,2'-azobis-2-methylbutyronitrile, 2,2'-dimethylazobisisobutyrate, 3,5-dihydroxymethylphenylazo-2-methylmalonodinitrile, 2,2'-azobis-2-methylvalonitrile, 4,4'-azobis-4-dimethylcyanovaleric acid, and 2,2'-azobis-2,4-dimethylvaleronitrile.

[0087] Suitable redox initiators include, for example, combinations of hydrogen peroxide-iron(II) salt, organic hydrogen peroxide-dimethylaniline, and cerium(IV) salt-alcohol.

[0088] Suitable radical photopolymerization initiators include known photopolymerization initiators such as alkylphenone-based photopolymerization initiators, α-aminoalkylketone-based photopolymerization initiators, and phosphine oxide-based photopolymerization initiators.

[0089] More specifically, radical photopolymerization initiators can be selected from and described from alkylphenone-based photopolymerization initiators such as 1-hydroxycyclohexylphenyl ketone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one.

[0090] Examples of suitable α-aminoalkyl ketone-based photopolymerization initiators include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, and 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)butan-1-one.

[0091] Suitable examples of phosphine oxide-based photopolymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. In addition, two or more types of these photopolymerization initiators may be added as a mixture.

[0092] Other suitable polymerization initiators may include dialkyl disulfides, such as tetraalkylthiuram disulfides, in which the SS bonds are readily decomposed by heat.

[0093] According to the embodiment, the cationic polymerization initiator may be selected from acids such as methanesulfonic acid, sulfuric acid, p-toluenesulfonic acid, and combinations thereof. Cationic photoinitiators can also be used.

[0094] The amount of cationic / radical polymerization initiator used is preferably in the range of 0.001 to 10% by weight, preferably 0.005 to 5% by weight, and more preferably 0.01 to 3% by weight, calculated relative to the total weight of the crosslinkable poly(alkylidene oxazolidone) formulation.

[0095] Use of poly(oxazolidone) derivatives in medical devices A poly(oxazolidone) compound selected from the poly(hydroxyoxazolidone) compound according to the first aspect of the present invention and the crosslinked poly(oxazolidone) compound according to the third aspect of the present invention can be used as a main component of the bulk composition of a medical device or as a coating on its surface. The poly(alkylideneoxazolidone) compound according to the second aspect of the present invention is also suitable in processes for manufacturing medical devices when used in crosslinked compositions, thereby resulting in the biocompatible crosslinked poly(oxazolidone) compound according to the third aspect of the present invention.

[0096] All poly(oxazolidone) derivatives according to the present invention are hemocompatible, and more specifically, the PHOx compounds according to the present invention are advantageously more hemocompatible than state-of-the-art isocyanate-based polyurethanes. They induce less coagulation and less platelet adhesion than isocyanate-based polyurethanes. The material further advantageously induces less bacterial adhesion than conventional materials used to manufacture catheters. In addition, the material has high mechanical resistance, exhibits high mechanical strength, adaptable elasticity, and, remarkably, high resistance in aqueous environments. These properties make it ideally suitable for use as a medical device when in contact with blood (or other fluids inside or outside the body).

[0097] Since thrombosis from medical devices significantly increases the risk of bacterial infection, this invention will also reduce infection, which is the second major complication of medical device use.

[0098] Medical devices also refer to non-implantable devices such as blood bags, wound healing products, and components of extracorporeal membrane oxygenation (EMU) systems. Furthermore, medical devices include patches for managing infarcted heart tissue.

[0099] In particular, medical devices comprising poly(oxazolidone) derivatives according to the first and third aspects of the present invention are catheters introduced into a host mammal to deliver fluids such as blood products, glucose solutions, and drug diagnostic agents. Catheters may also be used, for example, to treat blood, to drain urine from the bladder, or to collect blood from the vascular system for sample collection.

[0100] The catheters according to the present invention refer to urethral catheters, central venous catheters, cardiovascular catheters, neurovascular catheters, intravenous catheters, and special catheters, but also include endotracheal tubes, cannulas, ophthalmic catheters, etc. The catheters according to the present invention can be partially or entirely made from poly(oxazolidone) derivatives according to the first and third embodiments of the present invention.

[0101] Alternatively, the catheter according to the present invention may be partially or completely coated with a poly(oxazolidone) derivative.

[0102] In particular, medical devices containing poly(oxazolidone) derivatives include artificial heart valves such as polymer valves, mechanical valves, or bioprosthetic valves.

[0103] Artificial heart valves containing poly(oxazolidone) derivatives can be fabricated partially or entirely from poly(oxazolidone) derivatives.

[0104] Alternatively, the artificial heart valve containing the poly(oxazolidone) derivative may be partially or completely coated with the poly(oxazolidone) derivative.

[0105] A mechanical valve refers to a single-lobe or bi-lobe heart valve made of either pyrolytic carbon, or titanium coated with pyrolytic carbon and further coated with a poly(oxazolidone) derivative.

[0106] Bioprosthetic valves, also known as tissue valves, refer to bilobed or trilobed heart valves that are provided by a donor animal and have tissue components coated with poly(oxazolidone) derivatives.

[0107] Polymer valves refer to bilobed or trilobed heart valves that are made entirely or partially from poly(oxazolidone) derivatives.

[0108] The novel medical device containing the poly(oxazolidone) derivative according to the present invention, either as a coating on its surface or as a major component of the bulk composition of the medical device, advantageously exhibits higher blood compatibility and induces less coagulation and less platelet adhesion than medical devices containing isocyanate-based polyurethane.

[0109] The poly(oxazolidone) derivatives according to the present invention are advantageously biocompatible. They did not exhibit cytotoxicity when tested in vitro. They also showed antibacterial properties against bacterial adhesion. No necrosis was observed when tested in vivo in rabbits for up to 4 weeks.

[0110] The poly(oxazolidone) derivatives according to the present invention also exhibit long-term stability, such as up to 4 weeks, when tested in vitro and in vivo.

[0111] Process for preparing medical devices The poly(oxazolidone) derivatives according to the present invention can, advantageously, be processed into medical devices by various processing techniques.

[0112] When the poly(alkylidene oxazolidone) derivative of the present invention is in the form of a thermoplastic resin, the resin can be hot-pressed, molded, and / or extruded, and / or 3D printed. For example, cross-linked poly(oxazolidone), including medical devices, can be obtained by injection molding. Extrusion-based additive manufacturing / 3D printing techniques can be selected from fused deposition modeling / fusible filament 3D printing and direct ink writing.

[0113] Alternatively, the crosslinkable formulations of the present invention, comprising poly(alkylidene oxazolidone) derivatives, are in liquid form. A thiol and, optionally, a suitable radical and / or cationic initiator may be added to form a curable liquid resin. In the case of a photoinitiator, the resin may be processed (crosslinked) by light-based 3D printing techniques such as stereolithography. The liquid resin can be cured by UV light and / or visible light. This can be processed by digital laser printing.

[0114] Photocurable liquid resins can also be irradiated within a mold.

[0115] Liquid formulations of poly(oxazolidone) derivatives can also be processed by electrospinning techniques. This makes it possible to generate fibers from polymer solutions using various conductive collectors. Such fibers can be used as scaffolds for biomedical applications such as tissue engineering.

[0116] Advantageously, poly(oxazolidone) derivatives can also be reprocessed.

[0117] Advantageously, formulations containing poly(oxazolidone) derivatives and radical / cationic polymerization initiators (e.g., photoinitiators) are biocompatible. [Brief explanation of the drawing]

[0118] [Figure 1A]This figure shows the decrease in storage modulus G' (Figure 1A), loss modulus G'' (Figure 1B), and complex viscosity (Figure 1C) of a PHOx sample (PHOx4) with increasing temperature, as well as the complex viscosity versus frequency at different temperatures (Figure 1D), as demonstrated by an oscillatory temperature ramp experiment. [Figure 1B] This figure shows the decrease in storage modulus G' (Figure 1A), loss modulus G'' (Figure 1B), and complex viscosity (Figure 1C) of a PHOx sample (PHOx4) with increasing temperature, as well as the complex viscosity versus frequency at different temperatures (Figure 1D), as demonstrated by an oscillatory temperature ramp experiment. [Figure 1C] This figure shows the decrease in storage modulus G' (Figure 1A), loss modulus G'' (Figure 1B), and complex viscosity (Figure 1C) of a PHOx sample (PHOx4) with increasing temperature, as well as the complex viscosity versus frequency at different temperatures (Figure 1D), as demonstrated by an oscillatory temperature ramp experiment. [Figure 1D] This figure shows the decrease in storage modulus G' (Figure 1A), loss modulus G'' (Figure 1B), and complex viscosity (Figure 1C) of a PHOx sample (PHOx4) with increasing temperature, as well as the complex viscosity versus frequency at different temperatures (Figure 1D), as demonstrated by an oscillatory temperature ramp experiment. [Figure 2] This represents the hemolysis rate in red blood cells after 3 hours of direct contact with PU and PHOx / Net / Can disks, as evaluated by absorbance measurement of the supernatant. [Figure 3] This represents the generated nicotinamide adenine dinucleotide, calculated from the lactate dehydrogenase activity of human platelets attached to the PU and PHOx / Net surfaces after a 2-hour incubation, as evaluated by a colorimetric assay. *p ≤ 0.05, standard one-way ANOVA. [Figure 4] This represents the coagulation endpoint time of platelet-deficient plasma after 2 hours of direct contact with PU and PHOx / Net disks. [Figure 5] This represents the metabolic activity of human fibroblasts (HFF-1) after 24 hours of indirect contact with PU and PHOx / Net / Can disks, as assessed by a fluorescence (resazurin) assay. [Figure 6]This represents the metabolic activity of human fibroblasts (HFF-1) after 24 hours of direct contact with PU and PHOx / Net / Can disks, as assessed by a fluorescence (resazurin) assay. *p ≤ 0.05, standard one-way ANOVA. [Figure 7] This represents the metabolic activity of human fibroblasts (HFF-1) after 7 days of direct contact with PU and PHOx / Net / Can disks, as assessed by a fluorescence (resazurin) assay. [Figure 8] This represents the measurement of the time required for bacterial activity to reach its peak in populations of S. epidermidis attached to PU and PHOx4 disks. **p ≤ 0.01, independent t-test. [Figure 9] This shows the scoring of different inflammatory parameters in the skin tissue surrounding PU and PHOx4 discs after 1 week of subcutaneous implantation in rabbits. ***p ≤ 0.001, ANOVA with Tukey's multiple comparison test. [Figure 10] This shows the scoring of different inflammatory parameters in the skin tissue surrounding PU and PHOx4 discs after 4 weeks of subcutaneous implantation in rabbits. ***p ≤ 0.001, ANOVA with Tukey's multiple comparison test. [Examples]

[0119] Example 1. Synthesis of poly(hydroxyoxazolidone) The synthesis of poly(hydroxyoxazolidone) (PHOx) is carried out by polyaddition between α-alkylidenebis (cyclic carbonate) and polymer diamine, as outlined below. [ka]

[0120] The α-alkylidenebis (cyclic carbonate) compounds used in Example 1 are as follows (BisαCC1 (left) and BisαCC2 (right)). [ka]

[0121] The polymer diamines used in Example 1 are as follows (PPG-NH2 (left) and PDMS-NH2 (right)). [ka]

[0122] Synthesis of poly(hydroxyoxazolidone) Poly(hydroxyoxazolidone) (PHOx) was synthesized as follows: Bis(α-alkylidene cyclic carbonate) (BisαCC1, 2.016 g, 8 mmol, 1 equivalent) was weighed into a 100 mL round-bottom flask and magnetically stirred with 8 mL of dry CH2Cl2. Then, poly(dimethylsiloxane)bis(3-aminopropyl) terminus (PDMS-NH2, Sigma-Aldrich, average Mn=2,500 g / mol, 20 g, 8 mmol, 1 equivalent) was added using a syringe under a nitrogen atmosphere, and the solution was stirred at 80°C for 24 hours. 20-30 cSt (from ABCR)

number

[0123] PHOx1 (precursor BisαCC1 and PPG-NH2 400g / mol): 1H-NMR (400MHz, DMSO-d6) δ(ppm) = 5.94 (s,1H), 3.66-3.32 (m,12H), 1.92 (s,1H), 1.68 (d,3H), 1.36-1.20 (m,6H), 1.08-0.97 (m,9H).

[0124] PHOx6 (precursor BisαCC2 and PDMS-NH2 2500g / mol): 1H-NMR (400MHz, CDCl3) δ(ppm)=3.12(s,2H),1.96-1.19(m,10H),0.46(s,2H),0.17-0.00(s,117H).

[0125] The following is a reaction scheme for four different types of poly(hydroxyoxazolidone) compounds according to the present invention, synthesized in Example 1. [ka]

[0126] Table 1 below presents the properties of the synthesized poly(hydroxyoxazolidone) compound. Different characterization methods were used to evaluate the properties. Fourier transform infrared spectroscopy (FTIR). Fourier transform infrared spectra were collected using a diamond attenuated total internal reflection (ATR) device with a Nicolet IS5 spectrometer (Thermo Fisher Scientific). The spectra were collected at 4000–500 cm⁻¹. -1 The results of 32 spectra in the range were obtained in transmission / ATR mode.

[0127] Gel permeation chromatography (GPC). The apparent number-average molecular weight (Mn) of PPG-based polymers was determined by GPC in DMF with LiBr (2.17 g / L) at a temperature of 55°C (flow rate of 1 mL / min) using a PSS SECcurity2 autosampler liquid chromatograph calibrated with PS standards and equipped with three columns (PSS GAM 1000 Å (x2), 30 Å), a pre-column, a dual absorbance detector (Waters 2487), and a differential refractive index detector (Waters 2414). PDMS-based polymers were determined by GPC in chloroform at a temperature of 35°C (flow rate of 1 mL / min) using an isocratic pump (VE 1122, Viscotek), a set of two PLgel 5 μm MIXED-C ultra-high efficiency columns, a Shodex SE 61 differential refractive index detector, and a tunable wavelength ultraviolet (UV) detector (Spectra 100, Spectra-Physics).

[0128] Equilibrium Water Absorption (EWA) measurement. Each sample (previously weighed) was immersed in water at room temperature for 24 hours, after which the equilibrium water content of the material was measured. The EWA was determined by calculating the average of at least three values ​​obtained by the following equation: Swelling degree = (W s,w -W d ) / W d ×100% In the formula, W s、w This is the weight of the sample after it has swollen in water, W d This is the weight of the dry sample before it swells in water.

[0129] Swelling measurement. The degree of network expansion was calculated by immersing each sample (previously weighed in a dry state) in CHCl3 at room temperature and calculating the average of at least three values ​​determined by the following equation. Swelling degree = (W s -W d ) / W d ×100% In the formula, W s This is the weight of the swollen sample in CHCl3 (after the mass has stabilized), and W dThis is the weight of the dry sample before swelling.

[0130] Gel fraction measurement. The gel fraction of the network was calculated by comparing the weight of the dry sample before immersion in CHCl3 (before swelling) with the weight of the sample after immersion in CHCl3 at room temperature for 24 hours (swelling) and drying overnight at 120°C to remove the CHCl3. These are expressed by the following equation: Gel content = W d、f / W d ×100% It was determined by calculating the average of at least three values ​​obtained by the formula, but in the formula, W d、f This is the weight of the sample after immersion in CHCl3 and drying overnight at 120°C, W d This is the weight of the dry sample before swelling.

[0131] Thermogravimetric analysis (TGA) was performed using the TGA 2 model on a Mettler Toledo (0.005% weight accuracy and 1 μg resolution). Samples were placed under a nitrogen atmosphere (20 mL / min) and subjected to a first heating step of 30–100°C with a heating lamp at 20°C / min, followed by an isothermal step of 10 minutes at 100°C, and a second heating step of 100–500°C with a heating lamp at 10°C / min.

[0132] Mechanical properties were measured at a temperature of 25°C using a TA Instruments Q800 dynamic mechanical analyzer (DMA) in DMA controlled force mode. Dimensions: 25 × 5 × 0.5 mm 3 Rectangular specimens were tested at a selected starting distance between two 7 mm clamps. For each measurement, a 5-minute starting equilibrium was applied at 25°C before applying a force to the specimen with a 0.05 MPa / min ramp to its fracture. The Young's modulus (E), fracture stress (σ), and fracture elongation (ε) of the specimens were calculated by averaging at least three reproducible values. Specimens were analyzed in both dry and hydrated states (after immersion in water for 24 hours).

[0133] The complex viscosity of PHOx4 was determined at different temperatures by performing frequency sweep experiments on an ARES-G2 rheometer (TA Instruments) equipped with a stainless steel parallel plate shape (25 mm diameter). A 1 mm plate gap, 1% strain, and frequency scan of 0.1–100 Hz were set, and the PHOx4 disk was placed between the plates to fully fill the geometry. Oscillating temperature ramps (30–150°C) were also performed on PHOx4 using a ramp at 2°C / min. The same plates were used, with a 1 mm plate gap, 1% strain, and a frequency of 1 Hz. Before all measurements, the normal force was monitored and relaxed, and the data was analyzed using TRIOS® (TA Instruments) software. [Table 1] [Table 2]

[0134] PHOx4 and PHOx6 possess thermoplastic properties, and their contact angles were measured to evaluate their hydrophobicity. The contact angles were 105° and 95°, respectively, and thus superior to the 90° that indicates hydrophobicity. As shown in Table 1b, PHOx4 has low swelling in water, which is particularly desirable for implanted medical devices. 10% thermal decomposition temperature (T d、10% Its temperature is 437°C, exhibiting high thermal stability (relative to volatile compounds), making it advantageous for implantation in the human body.

[0135] PHOx4 and PHOx6 were mechanically tested in both dry and hydrated states. In the dry state, PHOx4 exhibited the best mechanical properties of the two polymers, with a Young's modulus of 2.5 ± 0.03 MPa, a breaking stress of 0.49 ± 0.06 MPa, and an elongation at break of 52.6 ± 11.2%.

[0136] The mechanical properties of PHOx4, measured after immersion in water for 24 hours, were only slightly affected compared to their properties in the dry state. Interestingly, they did not exhibit the dramatic decrease in mechanical properties that might have been expected. The Young's modulus was 1.6 MPa, the breaking stress was 0.18 MPa, and the elongation at break was 23.9%. This is of particular interest for applications in hydrated media, such as medical devices that come into contact with blood. The measured values ​​are comparable to those of natural tissues reported in the literature.

[0137] The vibrating temperature ramp allows us to evaluate at what temperature the storage modulus (G', Figure 1A) and loss modulus (G'', Figure 1B), as well as the complex viscosity (Figure 1C), of the polymer PHOx4 begin to decrease. The coefficients show initial values ​​of G' and G'' of 1.09 MPa and 0.15 MPa, respectively, at 30°C, and a high complex viscosity of 175,762 Pa.s. However, these parameter values ​​cross at 77°C (a value of approximately 0.01 MPa) before reaching a quasi-plateau above 100°C, with complex densities <100 Pa.s above this temperature, and begin to decrease dramatically at approximately 60-70°C. Complex viscosity was also measured at different temperatures by frequency sweep experiments (Figure 1D), which show that polymer viscosity decreases with temperature and its suitable value for reprocessing the polymer at relatively low temperatures (below 120°C) by different thermal manufacturing methods such as thermal extrusion, injection molding, and even additive manufacturing / 3D printing. Thus, PHOx4 can be processed into films, filaments, and various molded objects. A suitable processing temperature was found to be approximately 80°C.

[0138] Furthermore, fibrous PHOx4 films were produced by electrospinning a solution of PHOx4 in dichloromethane (0.667 g / mL) for a total of 3 hours on either a flat aluminum sheet or a honeycomb-patterned collector with either 3 mm hexagonal sides and a 7 mm thickness, or 1.3 mm hexagonal sides and a 5 mm thickness. The apparatus was an ND-S electrospinning machine, with the voltage initially set to 21 kV and increased by 1 kV every hour, a flow rate of 5 μl / min, and a distance of 17 cm from the needle collector. On the flat collector, fibers were deposited across the entire surface without preferential orientation, while on the hollow honeycomb-shaped collector, fibers were preferentially deposited at the edges. In fact, a higher fiber density can be observed at the edges than in the center, even though it still contains fibers deposited with non-preferential orientation. This type of architecture is particularly suitable as a scaffold for cell culture because the higher fiber density at the edges generally allows for certain mechanical support to the membrane, while the lower fiber density in the honeycomb center allows for the space necessary for cell growth. The average diameter of the deposited fibers was approximately 2.0–2.8 μm for all three types of collectors. Their uniform deposition, shape, and diameter indicate the success of electrospinning PHOx4 and processing it into a fiber mat.

[0139] Considering the thermoplastic properties of PHOx4 studied through rheological experiments, 3D printing of it by thermal extrusion was also carried out. To enable direct printing of PHOx4 pellets / granules, a fused granule extrusion (FGE) printer (Ender 3 NEO with retrofitted V4 pellet extruder) was selected. Pellet was prepared by cutting filament obtained via a twin-screw extruder at 70°C and 30 rpm. Two cooling fans were added to the printer to enable rapid cooling of the polymer and avoid heat creep. A bed set heated to 60°C was also used to increase the adhesion of the first printed layer on the constructed platform. The parameters were as follows: a 0.8 mm diameter nozzle was heated to 110°C and moved at a speed of 7.5 mm / s, with a fixed extrusion ratio of 1.2 and a fixed layer height of 0.2 mm. Finally, a 6-line skirt was used to achieve stable filament deposition. These parameters enabled the successful 3D printing of multi-layered objects at relatively low temperatures.

[0140] Next, in vitro stability under physiological conditions was tested by immersion in phosphate-buffered saline (PBS) for 8 weeks. The first step consisted of a visual inspection of the material, revealing no signs of discoloration or cracking. In fact, no morphological changes were observed in the structure of the PHOx4 specimens. Secondly, the pH of the PBS solution was measured weekly and showed no significant changes over time, consistently remaining close to 7.4 (Table 1c). Thirdly, the change in polymer weight over time was monitored, as weight loss indicates degradation. PHOx4 samples were weighed once a week. The average weight was maintained, and the water absorption capacity was maintained over time, indicating that the polymer was stable (Table 1d). [Table 3] [Table 4]

[0141] Example 2. Dehydration of poly(hydroxyoxazolidone) All poly(alkylidene oxazolidone) (POx) were synthesized by dehydrating their respective poly(hydroxyoxazolidone)-based precursors, as defined and obtained in Example 1.

[0142] Each sample was placed in a Teflon® mold and then placed in an oven at 130°C for 2 hours under conditions without solvent or catalyst. Next, the viscous sample was subjected to the following treatment: 1 Analysis was performed directly at the oven output using 1H-NMR, FTIR, and DSC. POx1 (obtained after dehydration of PHOx1): 1 H-NMR(400 MHz,DMSO-d6)δ(ppm)=4.39(s,1H),4.16(s,1H),4.02(s,1H),3.86(s,1H),3.48(s,1H),1.88(dd,4H),1.24(d,3H),1.02(q,9H). POx6 (obtained after dehydration of PHOx6): 1 H-NMR(400 MHz,CDCl3)δ(ppm)=4.06(dd,1H),3.91(dd,1H),3.35(qq,2H),1.72-1.51(m,4H),1.38(s,3H),0.51-0.42(m,2H),0.17-0.00(s,117H).

[0143] The following is a dehydration reaction similar to that performed in Example 2. [ka] [Table 5]

[0144] Example 3. Crosslinking of poly(alkylidene oxazolidone) Poly(alkylidene oxazolidone) was crosslinked either by photocrosslinking (the resulting network is then called Net) or by cationic crosslinking (the resulting network is then called Can).

[0145] Photocrosslinking was carried out by a photothiol-ene reaction with a polythiol at room temperature (rt) using POx, thanks to the presence of unsaturation introduced by the dehydration of its PHOx precursor. Crosslinking can be accelerated using any classical photoinitiator suitable for use in photothiol-ene reactions.

[0146] For the photothiol-ene reaction, all networks were synthesized according to the following procedure: Poly(alkylidene oxazolidone) was weighed in a small vial (e.g., unsaturated POx4, 1 g, 0.74 mmol, 1 equivalent) and solubilized in 500 μL of chloroform (≧99.8%, VWR Chemicals). In a separate vial, the photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO, 97%, Sigma-Aldrich, 0.0308 g, 0.07 mmol, 0.1 equivalent) was also weighed and dissolved in 100 μL of chloroform by stirring away from UV light. Next, trimethylolpropanetris (3-mercaptopropionic acid) (≧95%, Sigma-Aldrich, SH3, 0.0978 g, 0.24 mmol, 0.33 equivalents) was added to the BAPO solution. The BAPO-thiol solution was then transferred to the first container away from UV light, and the chloroform was removed under vacuum. The mixture was then poured into a flat Teflon® mold and irradiated with UV light for 15 minutes using an Omnicure Series 2000 lamp (200 W, Hg, 365 nm wavelength). The resulting network was then placed in a 120°C oven overnight to remove any residual traces of chloroform before analysis by various techniques. 2,2' Networks synthesized starting from -(ethylenedioxy)diethanethiol (SH2, 95%, Sigma-Aldrich, 0.0671g, 0.37mol, 0.5 equivalents), pentaerythritol tetrakis(3-mercaptopropionic acid) (>95%, Sigma-Aldrich, SH4, 0.090g, 0.18mol, 0.25 equivalents), and dipentaerythritol hexakis(3-mercaptopropionic acid) (>93%, TCI, SH6, 0.096g, 0.12mol, 0.17 equivalents) were prepared according to the same adapted protocol. The following describes the crosslinking of poly(alkylidene oxazolidone) and polythiol to a poly(oxazolidone) network. [ka]

[0147] For cation crosslinking, a covalent adaptability network (Can) was synthesized according to the following procedure: Poly(alkylidene oxazolidone) was weighed in a small vial (e.g., unsaturated POx4, 4.122 g, 3.05 mmol, 1 equivalent) and solubilized in 3 mL of chloroform (≧99.8%, VWR Chemicals). In a separate vial, catalyst methanesulfonic acid (MSA, ≥99.0%, Sigma-Aldrich, 0.0141 g, 0.15 mmol, 0.05 equivalents) and trimethylolpropanetris (3-mercaptopropionic acid) (≥95%, Sigma-Aldrich, SH3, 0.398 g, 1.00 mmol, 0.33 equivalents) were also weighed and dissolved in 1 mL of chloroform by stirring. Next, to initiate crosslinking, the MSA-thiol solution was transferred to the first vial and stirred magnetically for 15 minutes, followed by heating at 40-50°C for 2 minutes. The mixture was then placed in an oven overnight under vacuum at 100°C to remove any residual traces of chloroform and to carry out the crosslinking before being analyzed by various techniques.

[0148] Networks synthesized starting from 2,2'-(ethylenedioxy)diethanethiol (SH2, 95%, Sigma-Aldrich, 0.2728g, 1.5 mmol, 0.5 equivalents), pentaerythritol tetrakis(3-mercaptopropionic acid) (>95%, Sigma-Aldrich, SH4, 0.3656g, 0.75 mmol, 0.25 equivalents), and dipentaerythritol hexakis(3-mercaptopropionic acid) (>93%, TCI, SH6, 0.3915g, 0.5 mmol, 0.17 equivalents) were prepared according to the same compatible protocol, either by photocrosslinking (Net) or cationic crosslinking (Can), as shown in the table below.

[0149] Polythiol (R) used in Example 3 10 -SH x Suitable examples of these are dithiol (SH2), trithiol (SH3), tetrathiol (SH4), and hexathiol (SH6), as shown below. [ka] [Table 6] [Table 7]

[0150] Networks formed starting from PPG-type amine (Net1, 49°) showed a lower contact angle (>79°) than those containing PDMS segments. These values ​​are consistent with the hydrophilicity of these flexible segments, indicating that PPG is more hydrophilic than PDMS.

[0151] After dehydration, all the polymers became viscous, making it impossible to perform tensile tests on POx. However, once crosslinked, it was possible to measure the mechanical properties of the formed network again.

[0152] The PPG-based network Net1 exhibited a Young's modulus of 8.5 ± 0.2 MPa (dry) and reached the machine limit in terms of elongation without fracture.

[0153] Regarding the PDMS-based network, Net4 formed with SH3 exhibited dry mechanical properties of 5.60±0.25 MPa(E), 0.85±0.14(σ), and 44.51±6.90%(ε), demonstrating the flexibility of these elastomers.

[0154] Interestingly, once hydrated, the network did not exhibit the dramatic decrease in mechanical properties that might have been expected. For example, for Net4, the Young's modulus was 4.99 MPa, the fracture stress was 0.59 MPa, and the elongation at fracture was 39.31%. These measurements indicate that water has little effect on the network's mechanical properties. After immersion in water for 24 hours, all mechanical properties of the compound remained high.

[0155] This is particularly well suited to biomedical applications, such as in medical devices that come into contact with bodily fluids, such as blood.

[0156]

number

[0157] When compared together, photobridged networks formed from the same precursor (PHOx4), namely Net8 (with SH2), Net4 (with SH3), Net9 (with SH4), and Net10 (with SH6), exhibit mechanical properties that follow the same trend. In fact, Young's modulus and fracture stress increase with the number of thiol functional groups (from SH2 to SH4), while elongation at fracture decreases. An exception can be seen in the network formed with SH6 (Net10), which has lower values ​​than that of Net9 (with SH4), and this can be explained by the six thiol functions of the polythiol SH6. This indicates that it is possible to tune the mechanical properties by changing the thiol functions, which may be interesting depending on the desired application.

[0158] The same trend is observed in covalently adaptable networks, where Young's modulus increases with elongation at break, and elongation at break decreases in both dry and hydrated states from Can2 (formed with SH3) to Can3 (formed with SH4). Similarly, the same observation can be made for covalently adaptable networks (Can4) formed with SH6, as with photocrosslinking networks formed with SH6, because their mechanical properties are lower than those of Can3 (with SH4), due to the high polyfunctionality of the crosslinking agent and the lower crosslinking density resulting from the high viscosity of the solution. This also exhibits favorable modular mechanical properties.

[0159] Medical-grade PU (Carbothane®) was used as the reference material in all in vitro and in vivo hemodynamic / biocompatibility and antimicrobial tests. PU, as well as the synthesized polymer (PHOx / Net / Can), were cut into 5mm diameter discs. These discs were rinsed in 0.9% NaCl (w / v) for 72 hours (with daily NaCl solution refreshes) at 37°C under gentle agitation (100 rpm). Both surfaces of the discs were sterilized under UV light (15 minutes of exposure to both sides).

[0160] Example 4. In vitro blood compatibility: Interaction with blood components tested in hemolysis tests (red blood cells) Hemolysis test (red blood cells). Fresh human blood was collected from a healthy donor into citrate tubes (3.8% sodium citrate), and the first tube was discarded to avoid the influence of tissue factor. Whole blood (WB) was centrifuged at 150xg for 15 minutes to remove platelet-rich plasma (PRP). Red blood cells (RBCs) were resuspended in phosphate-buffered saline (PBS, Gibco, Thermo Fisher Scientific, USA) and centrifuged at 800xg for 10 minutes. The RBCs were washed two more times, and a final ratio of 1:7 RBC / PBS was used for the hemolysis test. PU and the synthesized polymer were incubated with RBC / PBS in an orbital shaker at 37°C for 3 hours at 100 rpm. A solution of RBC / dH2O (1:7) was prepared using distilled water (dH2O) and used as a positive control for hemolytic effect. After 3 hours of incubation, the RBC solution was centrifuged at 800xg for 15 minutes, the supernatant was transferred to a 96-well polystyrene plate, and the absorbance (λ) was measured using a microplate reader.

number

[0161] Standard practice for evaluating the hemolytic properties of materials describes three distinct categories: hemolytic substances with a hemolytic percentage greater than 5%; slightly hemolytic substances with a hemolytic index of 5% to 2%; and non-hemolytic substances with a hemolytic percentage less than 2% (Standard Practice for Assessment of Hemolytic Properties of Materials, ASTM F756-00, (2010), 5). According to these criteria, all polymers tested (PHOx4, Net1, Net4, Net5, Net8, Net9, Net10, Can1, Can2, Can3, and Can4) were non-hemolytic, similar to the PU criteria. In fact, the average hemolytic rate for all was well below 0.5% (see Figure 2).

[0162] Example 5. In vitro blood compatibility: Interaction with blood components (platelet adhesion) tested by lactate dehydrogenase activity. Platelet adhesion on polymer surfaces was evaluated using a lactate dehydrogenase activity (LDH) assay, which allows for the quantification of generated NADH. The Western blotting (WB) was centrifuged at 150xg for 15 minutes to collect platelet-rich plasma (PRP), and platelets were counted. The desired concentration (250,000 platelets / μL) was obtained via dilution in platelet-rich plasma (PPP). Polymer discs were incubated with platelets in an orbital shaker at 100 rpm for 2 hours at 37°C. After 2 hours of incubation, adherent platelets were washed with PBS and subsequently lysed with Triton-X100 (Merck, 1%). Lactate dehydrogenase (LDH) activity in the lysate was measured using a colorimetric assay kit from Sigma-Aldrich. LDH reduces nicotinamide adenine dinucleotide (NAD) to NADH, and absorbance measurement (λ) was performed.

number

[0163] The mean NADH levels generated on the PU surface were higher than those on PHOx4 and similar to those observed on Net1 / Net4 / Net5 disks (see Figure 3). The results indicate a very low level of platelet adhesion on the PHOx4 surface, suggesting lower thrombogenicity of this polymer than medical-grade PU. The other polymers, Net1, Net4, and Net5, induced platelet adhesion similar to that of PU.

[0164] Example 6. In vitro blood compatibility: Interaction with blood components tested by coagulation test (coagulation time) and plasma kallikrein-like activity. The coagulation test was performed as follows: PPP (CRYOcheck Pooled Normal Plasma (Cryopep, France)) was thawed at 37°C for 5 minutes and then incubated with a polymer disc. After 2 hours of incubation, human plasma coagulation time was measured via the inactivated partial thromboplastin time (NaPTT) test. NaPTT reagent (NODIA) was added to the PPP sample and incubated at 37°C for 1 minute. A calcium chloride solution (0.025 M) was added to the preheated sample, and the coagulation endpoint was measured using a Stago STart 4 instrument.

[0165] After incubating human plasma with PU and PHOx / Net disks, similar average coagulation times were found to be approximately 100 seconds (see Figure 4). Of the polymers tested, PHOx4 showed the longest coagulation time. Overall, none of the polymers tested induced more contact activation of coagulation than the PU standard.

[0166] Plasma kallikrein-like activity was also quantified during incubation with polymers. First, Tris buffer was prepared in-house by reconstituting the substrate (S-2302, Chromogenix) in dH2O and adjusting the pH to 7.8 at 25°C. PU and PHOx4 disks were incubated with PPP at 37°C for 2 hours. PPP alone was used as a negative control, while PPP incubated with Patrontin (Siemens) was used as a positive control. CaCl2, Tris buffer, S-2302, and acetic acid (acid stopped method) were sequentially added to the incubated plasma according to the timing and amount recommended by Chromogenix. Absorbance values ​​(λ

number

[0167] Example 7. In vitro biocompatibility: Interaction with human fibroblasts via indirect contact (extract) Cell line and culture conditions. In vitro biocompatibility assays were performed using human foreskin fibroblasts (HFF-1). Cells were grown at 37°C in a humidified atmosphere containing 5% v / v CO2 in Dulbecco's modified Eagle medium (DMEM, Gibco, Thermo Fisher Scientific, USA) supplemented with 10% v / v fetal bovine serum (FBS, Gibco, Thermo Fisher Scientific, USA) and 1% v / v penicillin / streptomycin (Pen / Strep). The medium was refreshed every two days. When 90% confluence was reached, the cells were rinsed with 5 mL of PBS (37°C) and detached from the culture flask using 2 mL of trypsin-EDTA solution.

[0168] Indirect Contact (Extract). The cytocompatibility of synthetic polymers (PHOx / Net / Can) was initially evaluated using an indirect contact assay by incubating cells with extracts of materials prepared as described in ISO 10993-12:2004. Briefly, to prepare the extracts, sterile 5 mm polymer discs were incubated with DMEM in an orbital shaker at 100 rpm at 37°C for 24 hours. Cells were incubated at 1 × 10⁶ 5 Cells were seeded in 96-well plates at a density of cells / mL and incubated at 37°C for 24 hours in 5% v / v CO2. After 24 hours, when a cell monolayer had formed, extracts of the material were added according to ISO 10993-5:2009(E), and the cells were incubated for a further 24 hours. A solution of Triton(X-100) 0.1% v / v was used as a positive control for in vitro cytotoxicity.

[0169] In accordance with ISO 10993-5:2009(E)-Biological evaluation of medical devices-Part 5: Tests for in vitro cytotoxicity, (2009), a threshold of 70% of the metabolic activity percentage (when compared to CTL-) should be set to regard the material as non-cytotoxic. After 24 hours of incubation with the polymer extract, the results revealed a percentage higher than 70% for the synthesized PHOx / Net / Can, as well as for PU (see Figure 5). This indicates that the leached products of PHOx / Net / Can discs extracted for 24 hours were not cytotoxic to HFF-1 cells.

[0170] Example 8. In vitro biocompatibility: Interaction with human fibroblasts in direct contact Direct contact cells were cultured at 1×10 5細胞 / mLの密度で48ウェルプレートに播種し、5 % v / v CO₂ at 37°C for 24 hours. After 24 hours, when a cell monolayer was formed, sterile polymer discs (PHOx / Net / Can) were added to each well, and the cells were incubated for an additional 24 hours or 7 days. A 0.1% v / v solution of Triton (X-100) was used as the positive control for in vitro cytotoxicity.

[0171] After 24 hours of direct contact with the polymer discs, the results revealed a percentage higher than 70% for all test samples, the synthesized PHOx / Net / Can and medical-grade PU, except for Can3, for which the average metabolic activity was slightly below 70% (see Figure 6). When this direct contact was extended for 7 days, the metabolic activity was still higher than 70% for most of the synthesized PHOx / Net / Can, except for Net8, Can1, and Can3 (see Figure 7). Both indirect and direct contact assays showed that most PHOx / Net / Can were biocompatible in vitro.

[0172] Measurement of metabolic activity. Metabolic activity of fibroblasts was quantified via a resazurin-based assay after 24 hours or 7 days of indirect and direct contact with PHOx / Net / Can extracts and disks. To this end, the culture medium was removed from the wells, and fresh medium containing 10% v / v resazurin (10-oxide-7-oxofenoxazine-10-ium-3-oleate, Stemcell Technologies, Canada) was incubated with the cells at 37°C for 4 hours with 5% v / v CO2. The medium was then transferred to a black 96-well plate, and relative fluorescence units (RFU) were measured using a microplate reader (λ). ex

number

number

[0173] Example 9. Antimicrobial test: Adhesion of Staphylococcus aureus Bacterial strains and culture conditions. Bacterial adhesion assays were performed using Staphylococcus epidermidis (S. epidermidis) (ATCC35984). Two colonies were taken and incubated overnight at 37°C in 5 mL of trypsin-soybean broth (TSB, MilliPore, Thermofisher, USA) with stirring (190 rpm).

[0174] Surface antifouling properties. The antimicrobial potential of synthesized PHOx4 was evaluated by incubation of polymer discs containing bacterial suspensions. Sterilized 5 mm polymer discs of PHOx4 and control PU were incubated for 10 minutes. 5The polymer discs were incubated with a CFU / mL bacterial inoculum in TSB for 2 hours at 37°C under static conditions. After a 2-hour adhesion step, the polymer discs were rinsed with 500 μL of PBS to remove any non-adhering or poorly adhered bacteria. The discs with adhered bacteria were transferred to calWell optical-grade sterile plastic inserts (SYMCEL), and 100 μL of fresh TSB was added to each sample. The plastic inserts were then placed in titanium cups closed with titanium lids, and the metal ensemble was incubated in a calScreener instrument for 24 hours under static conditions at 37°C. This allows for calorimetry, a highly sensitive approach based on the first law of thermodynamics, to measure the minimum thermal change in the minimum sample volume.

[0175] Measurement of bacterial activity. Bacterial activity was measured by detecting the heat generated, a byproduct of the biological process. Heat is directly related to growth and heat generation rate relative to metabolic flux. Maximum heat flow and time to peak were measured.

[0176] Monitoring of adhering Staphylococcus epidermidis on polymer disks (PU and PHOx4) revealed that the average time to peak was longer for PHOx4 than for PU (Figure 8). These data indicate that the initial bacterial count on the PHOx4 disk (after removing non-adhering bacteria from the previous 2-hour pre-adhesion step) was lower than on the PU disk, thus demonstrating that PHOx4 exhibits anti-adhesion properties for bacteria compared to PU.

[0177] Example 10. In vivo biocompatibility: Subcutaneous implantation of PHOx4 in rabbits Animal models and housing conditions All procedures described were approved by the Ethics Review Committee.

[0178] In vivo biocompatibility assays were performed using female New Zealand White (NZW) rabbits aged 112–118 days (Charles River Laboratories, France). Rearing conditions conformed to ISO 10993-2 requirements. The animals were kept in a temperature and humidity controlled environment with free access to standard rabbit feed and tap water. The rabbits had an acclimatization period of at least one week and were examined every 24 hours.

[0179] surgery The surgery was performed under general anesthesia, in accordance with the recommended standards of ISO 10993-6, to minimize trauma to the implant site. After weighing the animals, anesthesia was induced by intramuscular injection of droperidol (0.625 mg / kg), xylazine (5 mg / kg), and ketamine (35 mg / kg) into the hind limbs. Hair was removed from the surgical area (dorsal) by shaving to prevent contact between the implant or wound surface and hair. The exposed skin area was disinfected, and the incision was opened to create pockets for each polymer disc. Sterilized PU and PHOx4 discs were placed subcutaneously, with at least 2 cm between different implants. The pockets were closed with at least two stitches using Prolene® sutures.

[0180] Post-operative procedures The awakening period in rabbits was typically shorter than one hour after implantation. Animals were monitored every 30 minutes on the day of implantation, and every 24 hours thereafter. Buprenorphine (0.05 mg / kg) was administered subcutaneously 24 hours after implantation. If the area around the closed wound became irritated, iodopvidone (isobetadine gel 10%, Mylan) was applied to the irritated skin.

[0181] Euthanasia, implant retrieval, tissue sampling One or four weeks later, the animals were anesthetized and euthanized, and the implants were removed along with the surrounding tissue. Euthanasia was performed on animals anesthetized by intracardiac injection of pentobarbital (200 mg / kg). The implants, along with the surrounding tissue, were fixed for 24 hours in a solution of paraformaldehyde (PFA, 4%) in PBS. The implants were then separated from the tissue before histological preparation. The tissue was dehydrated in a 70% ethanol solution (overnight at room temperature), then embedded in paraffin wax, sectioned, and stained with hematoxylin-eosin (H&E) and Masson's trichrome. Histological sections were analyzed and scored by pathology specialists.

[0182] Inflammation marker scoring Local effects were evaluated by comparing the histopathological response induced by PHOx4 (test specimen) with that induced by PU (used in medical devices with established clinical acceptance), according to ISO 10993-6. The biological response parameters analyzed included: degree of fibrosis / fibrous capsule; changes in tissue morphology; number and distribution of polymorphonuclear neutrophils (PMNs), lymphocytes, plasma cells, macrophages, and giant cells; presence, degree, and type of necrosis; tissue changes such as neovascularization or fatty infiltration; and material parameters such as fragmentation and / or presence of debris. The scoring procedure was based on the recommended specifications of ISO 10993-6 (Annex E, Tables E.1 and E.2). Comparisons between different inflammatory markers in PU or PHOx4 were performed by ANOVA with Tukey's multiple comparison test. The scoring results one week after implantation are shown in Figure 9. Overall, no actual necrosis was observed, or it was minimal. One parameter that showed a statistically significant difference between PU and PHOx4 was the degree of superior angiogenesis compared to PU. This represents an advantage for PHOx4, as excessive new blood vessel formation represents an undesirable marker in the context of inflammation and harmful foreign body reactions. Four weeks after implantation (see Figure 10), no necrosis was observed, all samples scored 0, and virtually no fat infiltration was observed. Interestingly, PU triggered significantly more fibrosis than PHOx4. Given that excessive fibrosis can impair the function of the medical device and ultimately lead to the retrieval and replacement of the implant, the observation of less fibrotic tissue on PHOx4 suggests that this polymer may be superior to PU in the context of implantation.

[0183] Furthermore, the implant maintained its mechanical and surface properties after four weeks, showing no signs of deterioration.

Claims

1. Formula (I) or (II): 【Chemistry 1】 A poly(hydroxyoxazolidone) compound corresponding to the above, During the ceremony, -R 1’ , R 2’ However, each independently represents a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, and most preferably a methyl group. -R 3 , R 4 However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R 5 , R 5’ , R 6 , R 6’ However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group. -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, which preferably has 1 to 20 carbon atoms, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further contains one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. - optionally, A and R in formula (I) 3 , and R 4 are linked to one another to form a cyclic structure -Optionally, R in equation (II) 5 and R 5’ , and / or R 6 and R 6’ However, they are each connected to each other to form a ring structure, -R 7 However, it is a polymer chain selected from polysiloxane or polyether, A poly(hydroxyoxazolidone) compound in which -n is an integer between 2 and 100, preferably 2 and 50, more preferably 2 and 25, and most preferably 2 and 15.

2. R 7 The poly(hydroxyoxazolidone) compound according to claim 1, wherein the polymer chain is selected from polysiloxanes having a molecular weight in the range of 900 to 30000 g / mol, preferably in the range of 1500 to 10000 g / mol, more preferably in the range of 2000 to 5000 g / mol, most preferably in the range of 2000 to 3000 g / mol, preferably polydimethylsiloxane (PDMS), or polyalkylene glycols having a molecular weight in the range of 230 to 10000, preferably in the range of 230 to 5000 g / mol, more preferably in the range of 300 to 4000 g / mol, most preferably in the range of 350 to 3000 g / mol, preferably polypropylene glycol (PPG) or polyethylene glycol (PEG), and a polyether selected from a combination thereof.

3. A formulation for preparing a poly(hydroxyoxazolidone) compound, wherein the formulation is - Equation (III) or (IV) 【Chemistry 2】 A polyfunctional cyclic carbonate (compound A) having at least two terminal α-alkylidene cyclic carbonate groups, During the ceremony, -R 1 , R 2 , R 8 , R 9 However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably hydrogen. -R 3 , R 4 However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R 5 , R 5’ , R 6 , R 6’ However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group. -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, which preferably have 1 to 20, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further contain one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. -Optionally, A and R in equation (III) 3 , and R 4 However, they are connected to each other to form a ring structure. -Optionally, R in equation (IV) 5 and R 5’ , and / or R 6 and R 6’ However, each is linked to the others to form a ring structure, and there is at least one polyfunctional cyclic carbonate (compound A), A formulation comprising at least one polyfunctional amine (compound B), wherein the polyfunctional amine is composed of a polymer chain, the polymer chain having at least two primary amine groups at its terminals, and the polymer chain is selected from polysiloxane or polyether.

4. The polyfunctional amine is a polymer diamine containing a polymer chain, wherein the polymer chain has at least two primary amine groups at its terminals, and preferably the polyfunctional amine is of the formula NH 2 -R 7 -NH 2 Corresponding to this, in the formula, R 7 The formulation according to claim 3, wherein it is composed of a polymer chain selected from polysiloxane or polyether.

5. The aforementioned polyfunctional amine is of formula NH 2 -R 7 -NH 2 Corresponding to this, in the formula, R 7 The formulation according to claim 3 or 4, wherein the present part is selected from polydimethylsiloxane (PDMS) having a molecular weight in the range of 900 to 30000 g / mol, preferably in the range of 1500 to 10000 g / mol, more preferably in the range of 2000 to 5000 g / mol, and most preferably in the range of 2000 to 3000 g / mol, or selected from polyethers having a molecular weight in the range of 230 to 10000 g / mol, preferably in the range of 230 to 5000 g / mol, more preferably in the range of 300 to 4000 g / mol, and most preferably in the range of 350 to 3000 g / mol, preferably selected from polyalkylene glycol, and more preferably selected from polypropylene glycol (PPG) and / or polyethylene glycol (PEG).

6. The formulation according to any one of claims 3 to 5, wherein the polyfunctional cyclic carbonate (compound A) is selected from at least one of the following compounds. 【Transformation 3】

7. A process for forming the poly(hydroxyoxazolidone) compound according to claim 1 or 2, wherein the process comprises at least a polyaddition step between the polyfunctional cyclic carbonate (compound A) and the polyfunctional amine (compound B) in the formulation according to any one of claims 3 to 6.

8. A process for forming a poly(alkylidene oxazolidone) compound, the process comprising a step of dehydrating a poly(hydroxyoxazolidone) compound according to at least claim 1 or 2, wherein the resulting poly(alkylidene oxazolidone) compound is of formula (V) or (VI): 【Chemistry 4】 Therefore, During the ceremony, -R 1 , R 2 , R 8 , R 9 However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably hydrogen. -R 3 , R 4 However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group. -R 5 , R 5’ , R 6 , R 6’ However, each independently represents hydrogen, or a C1-C20 alkyl group, preferably a C1-C10 alkyl group, more preferably a C1-C3 alkyl group, most preferably a methyl group, or an aryl group, preferably a phenyl group. -A is an organic linking group selected from linear, branched, saturated, unsaturated, cyclic and / or acyclic aliphatic, aromatic or aromatic aliphatic hydrocarbon groups, which preferably have 1 to 20, more preferably 1 to 12, and most preferably 1 to 8 carbon atoms, and optionally further contain one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes. -Optionally, A and R in equation (V) 3 , and R 4 However, they are connected to each other to form a ring structure. -Optionally, R in equation (VI) 5 and R 5’ , and / or R 6 and R 6’ However, they are each connected to each other to form a ring structure, -R 7 However, it is a polymer chain selected from polysiloxane or polyether, A process in which -n is an integer between 2 and 100, preferably between 2 and 50, more preferably between 2 and 25, and most preferably between 2 and 15.

9. A poly(alkylideneoxazolidone) compound obtained by the process described in claim 8.

10. A crosslinkable formulation for forming a network of poly(oxazolidone) compounds, wherein the formulation is - At least one poly(alkylideneoxazolidone) compound according to claim 9, -Formula R 10 -SH x At least one polythiol corresponding to, in the formula R 10 The polythiol is an organic group selected from C2 to C20 alkyl groups, and optionally further contains one or more functional groups selected from ethers, esters, amides, amines, carboxyls, sulfurs, halogens, and / or urethanes, where x is an integer from 2 to 8, preferably from 2 to 6. - A crosslinkable formulation comprising a radical and / or cationic polymerization initiator, optionally selected from a photopolymerization initiator and / or a thermal polymerization initiator.

11. The formulation according to claim 10, wherein the polythiol is selected from the following compounds. 【Transformation 5】

12. The formulation according to claim 10 or 11, wherein the radical polymerization initiator is a photopolymerization initiator selected from alkylphenone-based photopolymerization initiators, α-aminoalkylketone-based photopolymerization initiators, phosphine oxide-based photopolymerization initiators, and combinations thereof, and / or the polymerization initiator is preferably a cationic polymerization initiator selected from acids such as methanesulfonic acid, sulfuric acid, p-toluenesulfonic acid, and combinations thereof.

13. A process for producing a crosslinked poly(oxazolidone), the process comprising: providing a crosslinkable formulation according to at least one of claims 10 to 12; and optionally polymerizing the poly(alkylidene oxazolidone) compound and the polythiol in the presence of a suitable radical and / or cationic polymerization initiator to form a crosslinked poly(oxazolidone).

14. The process according to claim 13, wherein the step of polymerizing the poly(alkylidene oxazolidone) compound and the polythiol is a radical thiol-ene polymerization reaction carried out at room temperature and with irradiation of light, preferably selected from UV, red, and / or visible light, and the initiator is selected from radical photopolymerization initiators.

15. A cross-linked poly(oxazolidone) prepared according to claim 13 or 14.

16. Use of the poly(hydroxyoxazolidone) compound according to claim 1 or 2 in a medical device.

17. Use of the cross-linked poly(oxazolidone) of claim 15 in a medical device.

18. A medical device wherein the device contains, at least partially, a poly(hydroxyoxazolidone) compound according to claim 1 or 2, and the poly(hydroxyoxazolidone) compound in the device is preferably provided at least partially by coating, injection molding, extrusion molding, or an extrusion-based additive manufacturing technique.

19. A medical device wherein the device contains, at least partially, the crosslinked poly(oxazolidone) described in claim 15, and the crosslinked poly(oxazolidone) in the device is preferably provided at least partially by coating, in-mold irradiation, or light-based additive manufacturing techniques / stereolithography.